ASSOCIATION OF ALLERGIC RHINITIS WITH GENDER AND ASTHMA - Khan, Muhammad; Khan, Muhammad Alamgir; Shabbir, Faizania; Rajput, Tausif Ahmed (Journal of Ayub Medical College Abbottabad, 2013)
Background: Allergic rhinitis and asthma are chronic inflammatory conditions of airways sharing common pathophysiology. The two disorders have similar cellular responses, with different symptoms based on the differences in the physical structures involved. Studies have shown that allergic rhinitis has a major impact on asthma morbidity and that treating allergic rhinitis may also impact asthma control. The objective of this study was to determine association of allergic rhinitis with gender and asthma. Methods: In this cross-sectional study, 100 patients with allergic rhinitis and equal number of patients without allergic rhinitis were included. Patients were excluded if they were smokers or if they had respiratory infection within the month preceding the study. Allergic rhinitis was diagnosed on history, nasal smear and blood complete picture. In both groups, patients having asthma, pre-diagnosed by the physician were isolated and their frequency was calculated. Results: Ninety-two male and 108 female patients with mean age 30.72±12.58 were included in the study. Odds ratio for allergic rhinitis patients and asthmatics was 5.05 (p<0.05). Association of allergic rhinitis with gender was also statistically significant (p<0.05). Multiple regression analysis showed predictability of allergic rhinitis from asthma at p<0.05. Conclusion: Allergic rhinitis is significantly associated with gender and asthma. Keywords: allergic rhinitis, asthma, united airways disease hypothesis